(untitled) (Global Journal of Management and Business Research, 2017)
There is little research exists that examine the practice and problems of performance management and evaluation of employees in developing countries, especially in Ethiopia public sector. Therefore, this research was aimed to assess the practice and challenges of performance management and evaluation -in public sector in the case of finance and economic development department of Gamo Gofa zone. The study was conducted by using descriptive survey type in which all data relevant to the case was gathered and analyzed. In this study, both qualitative and quantitative data type were used. For that matter, the researchers used both primary and secondary data as a source of information. The study used systematic sampling technique in order select sample employees and purposive sampling technique to select representative officials and experts. In line with this, 40 sample size was selected from 68 total population.